Legal culture of journalists in the contemporary informational and legal space - Banakh, Serhii; Savicka, Viktoria (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The concept of journalist legal culture in the modern information and legal space are analyzed in article. The basic requirements for a journalist who writes on legal issues are determined.